Leadership And The Knowledge Ecosystem: Revisiting And Reconceptualizing The KMBOK Model - McFarlane, Donovan A. (Journal of Knowledge Management Practice, 2010)
This paper examines the idea of the Knowledge Ecosystem as developed from and around the Knowledge Management Body of Knowledge (KMBOK) model and concept by McFarlane (2008). The author explores the KMBOK and reconceptualizes the model as representative of the total body of knowledge and practices constituting the field of Knowledge Management (KM) in organizations or knowledge communities and shaped by cultural, political, economic, and legal factors to create a Knowledge Ecosystem reflective of the increasingly interconnected global economy or business ecosystems in which organizations and individuals operate. The author maps out and defines the Knowledge Ecosystem diagrammatically and explains its link to organizational systems, structures, and processes, and explores the roles and functions of leadership as a major factor in leading the knowledge organization through effective understanding and application of an Organizational Knowledge SWOT Analysis (OK-SWOT-A) in organizational knowledge building and development. The concepts of value, quality, efficiency, effectiveness, organizational learning, and competitive intelligence are also examined in relation to the knowledge building and development process.